2016
DOI: 10.4314/ejhs.v26i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Electronic information sources access and use for healthcare services in governmental and non-governmental hospitals of western Oromia, Ethiopia: A cross sectional study

Abstract: BACKGROUND: Access to and use of electronic information sources for clinical decision is the key to the attainment of health related sustainable goals. Therefore, this study was to assess Electronic Information Sources (EIS) access and use for healthcare service among hospitals of Western Oromia, Ethiopia, 2013. MATERIALS AND METHODS: A descriptive study design with quantitative and qualitative data collection methods was employed. Study subjects were selected by using simple random sampling technique. Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, utilization of EHIRs in this study was higher than a study done in western Oromia (42%). 23 This discrepancy might be due to difference in study settings, eg, nongovernmental and primary hospitals. Another possible explanation could be the difference in study period, which was conducted 4 years prior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, utilization of EHIRs in this study was higher than a study done in western Oromia (42%). 23 This discrepancy might be due to difference in study settings, eg, nongovernmental and primary hospitals. Another possible explanation could be the difference in study period, which was conducted 4 years prior.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of the study was determined using a single population-proportion formula by assuming 42% of health professionals utilized EHIRs 23 with a 10% nonresponse rate: and 166 from Tibebe Ghion Specialized Teaching Hospital. To ensure fair distribution of the total sample, stratified simple random sampling was applied for each hospital based on field of profession, and then using simple random sampling study participants were selected.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…While result from Ayder hospital showed that almost all, 95% use EMR system in the hospital, where, almost all 92% of units are organized with EM system (10). The use of EMR system among health professional in western Oromia was found to be 42% (29). In addition about 70.8% of health care providers from northern Ethiopia use electronic medical record (18).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using self-administered structured questionnaire which include information on socio-demographic, Organization and Technology related factors as well as knowledge, attitude and utilization of electronic medical record. The questionnaire were adopted from previous studies (10,25,(27)(28)(29). The questionnaire were prepared in English language.…”
Section: Data Collection Instrument and Techniquementioning
confidence: 99%